Outcome of patients with non‐ischaemic cardiogenic shock supported by percutaneous left ventricular assist device. (23rd August 2021) - Haurand, Jean M.; Haberkorn, Sandra; Haschemi, Jafer; Oehler, Daniel; Aubin, Hug; Akhyari, Payam; Boeken, Udo; Kelm, Malte; Westenfeld, Ralf; Horn, Patrick
Abstract: Aims: Percutaneous left ventricular assist devices (pVADs) are used to haemodynamically stabilize patients with cardiogenic shock (CS) caused by acute myocardial infarction (AMI). One out of every two patients has a non‐ischaemic cause of CS, and these patients differ profoundly from patients with AMI‐related CS. We assessed the usefulness of pVAD support for patients with non‐ischaemic CS. Methods and results: We analysed 106 patients with CS and Impella® support between 2015 and 2018. CS was non‐ischaemic in 36 patients and AMI‐related in 70 patients. Compared with the AMI group, those in the non‐ischaemic group were significantly younger [median age 62 (50.8, 70.8) years vs. 68 (58.0, 75.5) years, P  = 0.007] and had more patients with severely reduced left ventricular function (94% vs. 79%, P  = 0.035) and worse glomerular filtration rate [45 (27, 57) mL/min vs. 60 (44, 78) mL/min]. Propensity score matching yielded 31 patients with non‐ischaemic CS and 31 patients with AMI‐related CS, without a difference in baseline laboratory values or comorbidities. In both groups, pVAD support was performed along with haemodynamic stabilization, reduction of catecholamines and normalization of lactate levels. In 7 days, systolic blood pressure increased from 91 (80, 101) mmHg at baseline to 100 (100, 120) mmHg in the non‐ischaemic CS group ( P  = 0.001) and 89 (80, 100) mmHg at baseline to 112 (100, 128) mmHg in the AMI‐related CS group ( P  = 0.001). Moreover, in 7 days, the need of catecholamines (calculated as vasoactive‐inotropic score) decreased from 32.0 (11.1, 47.0) at baseline to 5.3 (0, 16.1) in the non‐ischaemic group ( P  = 0.001) and from 35.2 (18.11, 67.0) to zero (0, 0) in the AMI‐related CS group ( P  = 0.001). Lactate level decreased from 3.8 (2.8, 5.9) mmol/L at baseline to 1.0 (0.8, 2.1) mmol/L ( P  = 0.001) in the non‐ischaemic CS group and from 3.8 (2.6, 6.5) mmol/L to 1.2 (1.0, 2.0) mmol/L in the AMI‐related group ( P  = 0.001). In the non‐ischaemic CS group, eight patients (25.8%) were upgraded to veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) or long‐term mechanical circulatory support. Two of these upgraded patients received heart transplantation. In the AMI group, eight patients (25.8%) were upgraded to VA‐ECMO or long‐term mechanical circulatory support. Ninety‐day survival did not significantly differ between the groups (non‐ischaemic CS group 48.4%, AMI‐related CS group 45.2%, P  = 0.799). Conclusions: pVAD support is useful for haemodynamic stabilization of patients with non‐ischaemic CS and is valuable as a bridge to patients' recovery or long‐term left ventricular support and heart transplantation.